The Effect of a Mobile-Based Nutrition Education Module on Improving Feeding Practices and Nutritional Status of Children under Five in Urban Slums - Risnati Malinda; Chatarina Suryaningsih; Rahmah Juliani Siregar; Sri Sumarni; Emdat Suprayitno (International Journal of Public Health Excellence (IJPHE), 2026)
Background: Inappropriate feeding practices and high malnutrition rates among children under five remain critical public health issues in urban slums, where access to nutrition information is limited. Mobile health (mHealth) interventions offer a promising platform for delivering nutrition education. Objective: This study aimed to evaluate the effect of a mobile-based nutrition education module on improving feeding practices and nutritional status of children aged 6–23 months in urban slums. Methods: A quasi-experimental pretest-posttest control group design was employed. A total of 120 mother-child pairs were purposively selected and allocated into an intervention group (receiving a 12-week mobile-based module, n=60) and a control group (receiving conventional lectures and leaflets, n=60). Feeding practices (minimum dietary diversity, meal frequency) were assessed using structured questionnaires, while nutritional status was measured through anthropometry (weight-for-age, height-for-age, weight-for-height z-scores). Data were analyzed using paired t-test, independent t-test, and ANCOVA (p<0.05). Results: The intervention group showed significantly greater improvements in feeding practice scores compared to controls (p<0.001). Moreover, stunting prevalence decreased from 32% to 18%, and wasting from 15% to 7% in the intervention group, with significantly better WAZ and HAZ z-scores than the control group (p<0.05). Conclusion: The mobile-based nutrition education module effectively improved maternal feeding practices and child nutritional status in urban slums. This innovation offers a scalable, low-cost solution for addressing childhood malnutrition in underserved populations.